A new hermetic sealing method for ceramic package using nanosilver sintering technology. (February 2018) - Zhang, Hao; Liu, Yang; Wang, Lingen; Fan, Jiajie; Fan, Xuejun; Sun, Fenglian; Zhang, Guoqi
Abstract: High reliable packaging materials are needed for electronics when they work at harsh environments. Among which, the nanosilver material has been widely studied and applied in power electronics due to its low processing temperature and high reliability. This paper investigates the bonding properties of nanosilver sintered hermetic cavity. There are two kinds of lids used in this study, including copper lid and silicon lid. The X-ray and C-Mode Scanning Acoustic Microscopy (C-SAM) results revealed that delamination tended to happen in Cu lid sintered cavity as the recovery of deformed Cu lid was hindered by sintered dense Ag layer. However, no delamination or cracks were found in Si lid sintered cavity. Finite element analysis (FEA) method was used to investigate the effects of lid materials on the stress distribution of lid. The results indicated that the Cu lid sintered cavity showed a much higher stress than the Si lid sintered cavity under the sintering parameters of 250 °C and 10 MPa. There is no obvious change in the stress distribution areas on Cu lid with the increasing of pressures from 5 to 30 MPa. However, the distribution area of stress on Si lid expanded obviously only when the sintering pressure increased to 30 MPa. With the increase of sintering pressures from 5 to 30 MPa, the maximum stresses on Cu lid are almost the same, while increasing trend was found on Si lid. Highlights: Nanosilver sintering technology was used for hermetic sealing. Bonding quality was evaluated by both experiment and simulation method. Cu lid has a much higher maximum stress than Si lid after sintering. Si lid sintered cavity showed better bonding quality than Cu lid sintered cavity in this work.